The Evolution of Parallel Electron Temperature in Magnetospheric Reconnection Inflows - Daniel J. Gershman; Li‐Jen Chen; Ari Le; Jason Shuster; John C. Dorelli; Jonathan Ng; Barbara Giles; Adolfo F. Viñas; Roy Torbert; James L. Burch (Geophysical Research Letters)
Abstract Using data from NASA's Magnetospheric Multiscale mission captured in a reconnection inflow on the magnetospheric side of Earth's dayside magnetopause, we find a region where the heat flux density gradient term balances the parallel compression term in the electron parallel temperature equation. Combining these observations with analysis of the generalized fluid equations indicates that such a behavior represents a quasi‐isothermal region, where cold magnetosheath beams that have transported across the magnetopause introduce non‐zero gradients in parallel heat flux density. This region should prevail near dayside reconnection X‐lines in inflows on the magnetospheric side due to the formation of mixed electron distributions and increased parallel temperatures that arise from three‐dimensional boundary dynamics.